The unique roles of IFE-1, a germline-specific isoform of eukaryotic translation factor 4E, during gametogenesis - Henderson, Melissa Anne (East Carolina University, 2009)
Fertility and embryonic viability are measures of efficient germ cell growth and differentiation. During oogenesis, spermatogenesis and embryogenesis cells initially proliferate then differentiate into specific tissues. New proteins are required for both cell growth and differentiation, requiring qualitative and quantitative changes in protein synthesis. During late gametogenesis and early embryogenesis the expression of the appropriate proteins is a primarily due to translational control. Translational control of mRNAs is mediated in part by eukaryotic initiation factor 4E (eIF4E). eIF4E binds the methylated 5' cap of mRNA and recruits it to the ribosome. The nematode worm C.elegans expresses five isoforms of eIF4E (termed IFE-1 through 5). IFE-1 is expressed primarily in the germline and is the only isoform that associates with P granules by binding directly to PGL-1. P granules are ribonucleoprotein particles (RNPs) that contain stored mRNAs and proteins needed for oogenesis and early embryogenesis. Using a strain that lacks IFE-1, I assessed the translational efficiency of maternal mRNAs bound and not bound to P granules by polysome fractionation. Translation of pos-1, pal-1, mex-1, oma-1, ced-4 and glp-1 mRNAs was inefficient in the ife-1 strain relative to wild type worms. GAPDH (gpd-3) mRNA translation was not affected. We also observed differences in the pattern of expression of the MEX-1 protein during oogenesis. In males, secondary spermatocytes failed to complete cytokinesis at 25°C in absence of IFE-1. Males deficient of IFE-1 therefore lacked mature sperm. In addition, ife-1 spermatocytes prematurely accumulated pro-apoptotic CED-4, homolog to mammalian Apaf-1, during spermatogenesis. In ife-1 worms fertility was decreased by 80% due to decreased viability of both oocytes and spermatocytes. Our data indicate two unique roles for eIF4E (IFE-1 isoform) in late oogenesis and spermatogenesis. We suggest that IFE-1 preferentially recruits regulated mRNAs at critical times during germ cell development.
Keywords: Biology, Molecular; Biochemistry; Molecular biology; Chemistry, Biochemistry